Schizophrenic seas and the Caribbean trans-nation - Boyce-Davies, Carole (2019)
Two concepts which appear titularly, orient this paper – “Schizophrenic Seas” and the “Trans-Nation.” “The Schizophrenic Sea” is Wilson Harris’s term which appears in his classic collection of essays, The Womb of Space. The “trans-nation” is Bill Aschroft’s attempt to revise the over-reaching framing of the post-colonial. For this paper, I propose to bring these two concepts together, as constitutive of each other. They move in different directions, but allow for a series of returns to unsettled boundaries, redefined sea-scapes and land-scapes definitely given the nature of island instability and the effects of environmental turns, creating a Caribbean-trans nation that also in my reading redefines Caribbean space.